Pengaruh Pemasaran Hijau Dan Kepribadian Merek Terhadap Citra Merek Dan Kepercayaan Merek Pada Produk Fashion “Kana Goods” - Syachruddin, Anisah Inas (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to determine how green marketing and brand personality affect brand image and brand trust in “Kana Goods” fashion products. This research was conducted by testing 70 samples of respondents who live in East Java and are between 20-24 years old. This research method is quantitative using an online questionnaire. The variables used are green marketing, brand personality, brand image, and brand trust. The data analysis technique used is multivariate analysis (canonical correlation) with SPSS software. Based on the results of the analysis, it shows that green marketing has a significant positive effect on brand image, green marketing has a significant positive effect on brand trust, brand personality has a significant positive effect on brand image, brand personality has a significant positive effect on brand trust, green marketing and brand personality have a significant positive effect on brand image, green marketing and brand personality have a significant positive effect on brand trust. As for suggestions for future researchers to further explore other factors that influence brand image and brand trust variables in order to gain a stronger and more comprehensive understanding and insight into these two variables.